Research on the pathways of empowering ideological and political education in universities with excellent traditional Chinese culture in the age of artificial intelligence - Wu, Yang (ITM web of conferences, 2025)
The application of artificial intelligence (AI) technology in the new era has brought significant changes to the development of various industries and sectors in society. This approach can strengthen college students' cultural identity, helping them establish correct worldviews, values, and outlooks. Leveraging the informational technology advantages of the AI era, such as the internet, big data, cloud computing, new media, and we-media, this paper delves into and develops resources from China's excellent traditional culture. By innovatively exploring pathways for ideological and political education in colleges and universities, it will promote the informatization of teaching reform in this field and also facilitate the inheritance and protection of China's excellent traditional culture.